Epidemiology of spinal cord injuries in three selected counties in Kenya - George M. Muli; Veronica Ntsiea; Natalie Benjamin-Damons; Nassib Tawa (South African Journal of Physiotherapy)
Background: Spinal cord injury (SCI) presents a significant health challenge, characterised by damage to the spinal cord resulting from trauma, inflammation, tumours or other aetiologies. This injury often leads to a range of debilitating consequences, including loss of motor function, sensation, sphincter control and autonomic nerve function below the site of injury, as well as challenges with self-care and performance of instrumental activities of daily living (ADLs).